Conflict Management in Educational Organizations: Strategies and Solutions - Rian Hidayat; Zubeir Ahmad Nasution; Salfen Hasri; Sohiron (Journal of Practice Learning and Educational Development, 2025)
Conflict is an inherent aspect of organizational life, including within Islamic educational institutions. While often viewed negatively, conflict can foster innovation and performance improvement if managed effectively. This study aims to identify appropriate conflict management strategies for Islamic educational institutions through a literature review of conflict and negotiation theories. A descriptive qualitative approach was employed, utilizing library research from various academic sources. The findings indicate that strategies such as SWOT analysis, win-win solutions, and integrative negotiation can be harmonized with Islamic values such as tabayyun (clarification), islah (reconciliation), and ukhuwah islamiyah (Islamic brotherhood). The integration of modern management theory with Islamic principles proves effective in facilitating fair, constructive, and sustainable conflict resolution. These insights are expected to serve as practical guidance for educational leaders in managing conflicts wisely and professionally.